The rDNA Diversity, Interseasonal Dynamic, and Functional Role of Cyanobacteria Synechococcus in the Sub-Arctic White Sea - Tatiana A. Belevich; Irina A. Milyutina; Olga V. Vorob’eva; Aleksey V. Troitsky (Plants)
Planktonic unicellular cyanobacteria are the dominant biomass producers and carbon fixers in the global ocean ecosystem, but they are not abundant in polar seawater. The interseasonal dynamics of picocyanobacterial (PC) abundance, picophytoplankton primary production, and phylogenetic diversity of PC Synechococcus were studied in the sub-Arctic White Sea. The PC abundance varied from 0.2–0.3 × 106 cells/L in February to 5.2–16.7 × 106 cells/L in July. Picophytoplankton primary production ranged from 0.22 mg C/m3 per day in winter to 11.32 mg C/m3 per day in summer. Synechococcus abundance positively correlated with water temperature and river discharge that increased in recent years in the White Sea. Phylogenetic analysis of the 16S rRNA gene and ITS region clone libraries from the White Sea and Barents Sea eDNA revealed picocyanobacterial sequences related to marine Synechococcus subclusters 5.1-I, 5.I-IV, 5.2, and 5.3. All Synechococcus S5.1-I were common in the White and Barents seas and were consistently present in the picophytoplankton composition throughout the year. Synechococcus S5.2 and S5.3 appear in the PC community in summer, suggesting their river origin, and Synechococcus S5.1-IV inhabits only the Barents Sea and was not detected in the White Sea. A unique Synechococcus phylotype was revealed. It is expected that the increase in the abundance of PC and their increasing role in ecosystem functioning, as well as the enrichment of the species composition with new phylotypes in the semi-enclosed sub-Arctic White Sea, which is vulnerable to the effects of climate change, will be characteristic of all Arctic seas in general.